Frequency of Hypertension in Children Presenting at Combined Military Hospital Malir Cantt Karachi - Zaidi, Syed Taqi Hassan; Maqsood, Almas; Ali, Arshad; Saba, Ameena; Ali, Wasif Shujaat; Afzal, Warda (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of hypertension in our children and explore its relation to obesity to emphasize the importance of routine blood pressure check-ups in outpatient departments and clinics. Study Design: Cross-sectional study. Place and Duration of Study: Pediatric Outpatient Department and Child Ward of the Combined Military Hospital Malir Cantt Karachi Pakistan, from May to Dec 2020. Methodology: A total of 1000 children of 3-13 years selected on consecutive sampling methods with no history of hypertension were enrolled. Three blood pressure readings were recorded using an aneroid sphygmomanometer using the standard protocol, and their weight and height were measured to calculate their BMI. Results: Out of 1000 children, 62 (6.20%) were found hypertensive, out of which 42 (67.7%) were male, and 20 (32.3%) children were females. Overall 42/622 (6.75%) male children and 20/378 (5.87%) female children developed hypertension. Obesity was found in 6.45% of positive cases, while 3.22% of hypertensive children were overweight. The frequency of hypertension linearly increased with increasing age. In addition, 12.9% of cases had a positive family history of hypertension. Conclusion: The frequency of hypertension in the Pediatric population was 6.20%. Male predominance was found in hypertensive cases. Hypertension was more prevalent among children of preadolescent age. Obese and overweight children were more likely to develop hypertension than normal-weight children.